2008
DOI: 10.1177/0022487108315581
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher Educator's Role in Enhancing Teacher Quality

Abstract: Common sense suggests a good teacher matters. Personal experiences with inspirational and challenging teachers reinforce this notion. Research has also shown some teachers have a more significant impact on student achievement than others (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 11 publications
0
24
0
4
Order By: Relevance
“…These benefits include increased feedback and encouragement through personal attention, obtaining the exact help needed, closer monitoring of progress and better mastery of skills. More studies (Liston, Borko, & Whitcomb, 2008;Moran, 2008) also suggested that preferred teacher education applicants are those who hold experientially based knowledge of teaching as they enter program that strive to offer practica experiences that show case exemplary practices.…”
Section: Tutoringmentioning
confidence: 99%
“…These benefits include increased feedback and encouragement through personal attention, obtaining the exact help needed, closer monitoring of progress and better mastery of skills. More studies (Liston, Borko, & Whitcomb, 2008;Moran, 2008) also suggested that preferred teacher education applicants are those who hold experientially based knowledge of teaching as they enter program that strive to offer practica experiences that show case exemplary practices.…”
Section: Tutoringmentioning
confidence: 99%
“…Scholars define teacher leadership (TL) to include formal roles and informal roles such as leader of professional learning communities (PLC) or peer coach (Liston et al, 2008). TL is an umbrella term for work that encompasses three developmental foci among practicing teachers: (a) individual development; (b) collaboration; and (c) organizational development.…”
Section: Teacher Leadershipmentioning
confidence: 99%
“…An effective teacher is a term that refers to teacher ability to foster student achievements (Liston et al, 2008) which shifts focus on the achievement outcomes rather than qualifications. Teacher effectiveness is expressed most commonly in terms of student academic achievement, an element more easily (and less expensively) measured than some other essential outcomes of good education (Leu, 2005).…”
Section: Introductionmentioning
confidence: 99%